Traders Perception and Awareness on Financial Derivatives in Indian Stock Market - Selvaraj, N (International Journal of Business Management and Finance Research, 2021)
The Government of India has introduced Economic Policy in 1991 to implement structural reforms for reduce the imbalances. In India, Traders want maximum gain with minimum risk, so is the case with derivatives. Derivatives are among the forefront of the innovations in the financial markets and aim to increase returns and reduce risk. A derivative is a financial product which has been derived from another financial product or commodity. The derivatives do not have independent existence without underlying product and market. Derivatives are contracts which are written between two parties for easily marketable assets. Derivatives are gaining importance due to increased volatility in capital and foreign currency markets. RBI finds ways for healthy development of market and takes steps to popularise the use of derivative instruments, but still awareness about the derivative instruments and its uses are quite low. Hence, it is necessary to find out the level of awareness among investing public and if found low, how to create adequate awareness to encourage the use of derivative products as hedge tools. This study can be used by the regulating authorities and broker houses to increase awareness among the traders about derivatives. One should invest in secured and risk-free investments rather than high-risk, highly profitable investments. Tracking the market environment better with sound knowledge about a particular stock would result in better returns. Since many of the entities in this study are independent of each other, there is need to analyse on a buying decision specifically for respective stocks. People with less experience can also be high profit makers when decisions are based on intricate fundamental and technical analyses.